Treatment of an asymptomatic penetrating aortic ulcer in a young patient - Hakimi, Maani; Geisbüsch, Philipp; Groß-Weissmann, Marie-Luise; Hyhlik-Dürr, Alexander; Haußer-Siller, Ingrid; Tengg-Kobligk, Hendrik von; Böckler, Dittmar (Vasa, 2010)
We want to report and discuss the indication for open surgery for an asymptomatic penetrating aortic ulcer (PAU) in the era of thoracic endovascular aortic repair (TEVAR). A 31-year-old female presented with the diagnosis of an aneurysm in the distal aortic arch. With respect to the patients young age, the controversial status of connective tissue disorders and in the absence of concomitant disease, open repair was indicated. There was no proof of a mycotic plaque or connective tissue disease in the microbiological-, pathological analysis and at electron-microscopy. The patient was discharged on the thirteenth postoperative day. In spite of good preliminary results of TEVAR in PAU, in selective cases there is still an indication for open surgery.